2014
DOI: 10.1017/s1368980014002626
|View full text |Cite
|
Sign up to set email alerts
|

Breast-feeding support in Ireland: a qualitative study of health-care professionals’ and women’s views

Abstract: Objective: To examine women's experience of professional support for breastfeeding and health-care professionals' experience of providing support. Design: We conducted semi-structured qualitative interviews among women with experience of breast-feeding and health-care professionals with infant feeding roles. Interviews with women were designed to explore their experience of support for breast-feeding antenatally, in hospital and postnatally. Interviews with health-care professionals were designed to explore th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 37 publications
2
27
0
2
Order By: Relevance
“…Conflicting information given to mothers about breastfeeding is widely reported (Fox et al, 2015;Leeming et al, 2015;Whelan and Kearney, 2014). This study demonstrated the long-lasting effect of conflicting advice on most participants as they verbalised their confusion and anxiety over several diary entries.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Conflicting information given to mothers about breastfeeding is widely reported (Fox et al, 2015;Leeming et al, 2015;Whelan and Kearney, 2014). This study demonstrated the long-lasting effect of conflicting advice on most participants as they verbalised their confusion and anxiety over several diary entries.…”
Section: Discussionmentioning
confidence: 67%
“…The UNICEF UK Baby Friendly Initiative Standards (2012, p. 2) state that all staff must be educated "according to their role and the service provided" not just to prevent conflicting messages but also medicalisation of breastfeeding. Whelan and Kearney (2014) interviewing health professionals and breastfeeding women agreed that there was a necessity for all health professionals to receive training about breastfeeding in order to prevent conflicting messages and medicalisation of breastfeeding. Providing consistent support does not mean scrutinising mothers' parenting and breastfeeding skills.…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding is often regarded as a challenging demand of motherhood [ 4 ], particularly in Ireland, which has a long-reigning formula feeding culture [ 7 , 11 , 20 ] and widely reported inadequate breastfeeding support [ 21 , 22 , 23 ]. Women who breastfeed at 17 weeks post-partum are in the minority, with only one in five Irish women breastfeeding, exclusively or otherwise, at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, alternative methods such as "peer support" shall be spread among women. 30 Physicians must try to use every opportunity to provide guidance and assistance to women and community. In this regard, PHC centres are excellent places where health care providers have good opportunity to provide the services.…”
Section: Discussionmentioning
confidence: 99%